(untitled) (Colombia Medica, 1986)
A statistical study shows the distribution among 2000 Colombian subjects of the Egyptian, Greek, and Square morphotypes of the forefoot. The most frequent of these morphotypes is the square (56.3%), followed by the Egyptian (31.5%) and the Greek (11.8%); this distribution is independent of sex, age, and place of birth of the individuals. Among white individuals, the predominant morphotype is square (56.7%), while among the black ones predominates the Egyptian (47.5%). The distribution of the dermatoglyphic patterns in whirl, arch, and loop for the first toe or hallux is also presented, predominating among these individuals the loop (61.5%), followed by the arch (19.6%). The relation between these dermatoglyphic patterns and the forefoot morphotypes shows that the most predominant associations are those of the loop with the square (30.4%) and the Egyptian (21.3%) morphotypes, followed by the associations between the arch and the square forefoot (9.5%), the loop and the Greek forefoot (9.3%), the arch and the Egyptian forefoot (7.5%). The deformation in the first toe’s hallux valgus or lateral deviation is only present in 1.5% of individuals over 70 years of age (3.9%). The prevalence of hallux valgus in the square forefoot is 60.1%; in Greek, it is 30.3%, and in Egyptian, it is 3.3%.